PENGARUH KARAKTERISTIK KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA (Studi Kasus pada Perusahaan IPO di Indonesia Tahun 2011-2013) - Raisya Hayyu Mughni; Nur Cahyonowati (Diponegoro Journal of Accounting, 2015)
This study aims to examine the influence of the Audit Committee Characteristics and Audit Quality on Earnings Management. Variables tested in this study consisted of an audit committee characteristics are measured with audit committee size, financial expertise and the number of audit committee meetings. While audit quality as measured by the size of public accounting firm and industry specialist auditors.The sample used in this study were taken by purposive sampling method. After reduction with criteria set at 49 companies in the sample. Techniques of analysis in this study using linear regression analysis with SPSS version 16. This study is a replication study conducted by Norman Mohd et al (2007) and the development of research Ken Y. Chen et al (2006), with differences in the variables and samples. This difference occurs because of differences in data sources, this study used secondary data companies IPO in Indonesia in 2011-2013, while the research of Ken Y. Chen et al (2006) used secondary data, IPO in Taiwan.The  results  of  hypothesis  testing  indicate  that  the  variable  Financial  Expertise  of  Audit Committee members have a significant impact on Earnings Management. Meanwhile, the variable size of the Audit Committee, Number of meetings Audit Committee, Public Accounting Firm Size and Industry Specialist Auditor no significant effect on Earnings Management.